Frances Mateychuk’s Quilts : Mapping a Place - Shantz, Susan (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1994)
Quilting can be more than creating bedspreads from scraps. It is, for Frances Mateychuk, a farmer from Saskatchewan as well as for many other Canadian Women, a way of going through those long winter hours. Through Frances’s voice, the act of quilting takes all its meaning. More than utilisation objects, quilts can become, within a community, a way of creating links and sometimes a way of “disturbing” sexual stereotypes when husbands start to quilts, for example...Frances Mateychuk’s quilts map her life and space. They are her legacy to her family and community, by which she will be remembered.